Age at the onset of tobacco smoking in South Africa: a discrete-time survival analysis of the prognostic factors - Adeniyi Francis Fagbamigbe; Rachana Desai; Ronel Sewpaul; Ngianga-Bakwin Kandala; Derrick Sekgala; Priscilla Reddy (BMC, 2020)
Abstract Background While knowledge of onset of smoking tobacco, and associated risk factors can aid the formulation of evidence-based policy and interventions, such information is scarce in South Africa. We assessed age at onset of tobacco smoking in South Africa and identified its risk factors. Methods We analysed data of 15,316 respondents aged 15-98 years from the 2012 South African National Health and Nutrition Examination Survey. Descriptive statistics and survival analysis techniques were used alongside weighted percentages. Results Overall lifetime prevalence of smoking was 20.5%. Among the 3360 ever-smoked respondents, the overall median age at smoking onset was 18 years (Inter-quartile range (IQR) =5) with 2% starting before age 10 while 60% had smoked before age 20. Likelihood of tobacco smoking was higher among adolescents (<=20 years) and those aged 20-29 years than those aged > = 60 years, thrice higher among males, 29% higher among urban dwellers and thrice higher in Western Cape and Free State than in North West Province. The onset of tobacco smoking was earlier among males, wealthier and "coloured" people from Northern and Eastern Capes. Conclusion The onset of tobacco smoking peaked at 15-22 years and varied by province, sex, location, race and other characteristics. The age restrictions on smoking in South Africa has changed over time, coupled with the recent open and electronic advertisement of tobacco, and social media could have influenced the earlier onset of tobacco smoking in South Africa. Stricter regulations on tobacco-related advertisement and sales should be implemented.